Influence of Leadership, Organizational Climate and Job Satisfaction on Teacher Performance - Dedi Suhendro; Ilham Syahputra Saragih (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this study was to determine the influence of leadership on the performance of teachers in the State-Owned High School I Tanah Jawa, Simalungun Regency. To find out the influence of organizational climate on the performance of teachers in the State-Owned High School I Tanah Jawa, Simalungun Regency. To determine the influence of job satisfaction on teacher performance in the State-Owned High School I Tanah Jawa, Simalungun Regency. To find out the influence of leadership, organizational climate, and job satisfaction on the performance of teachers in the State-Owned High School I Tanah Jawa, Simalungun Regency. The sample in this research amounted to 55 teachers. Data analysis techniques in this research used descriptive analysis and multiple linear regression analysis. The results of this research explain that the leadership variable has a positive and significant influence on teacher performance by 33.27%. Organizational climate variables have a positive and significant influence on teacher performance by 43.30%. The job satisfaction variable has a positive and significant influence on teacher performance 42.34%. The variables of leadership, organizational climate, and job satisfaction have a positive and significant influence on teacher performance by 70.00%, while the remaining 30.00% is influenced by other factors not examined.